Characterization of Upper Indus Basin based on DEM Hypsometric Analysis - Ahmad, I.; Ahmad, Z.; Munir, S.; Rehman, Obaid ur; Ali, S. R.; Shabbir, Y. (The Nucleus, 2018)
Assessment of geomorphic stages of catchment areas within Upper Indus Basin (UIB) is carried out through analysis of hypsometry. Hypsometric curves were extracted for each sub-basin from Digital Elevation Model (DEM) of Shuttle Radar Topography Mission (SRTM). Parameters of the Hypsometric Integral (HI), statistical moments like skewness, kurtosis, density skewness and density kurtosis of the curves were also analyzed. Study concluded that UIB is comprised of sub-basins of differential characteristics i.e. young, moderate and well developed. There is a correlation of 0.76 between the basin size and the HI. None of the basins appear to be in Monadnock Stage. The topographic analyses of slope, aspect and percentage snow-cover and land cover classes also validate the high erosion potential of upper reaches of Indus basin.